Evaluation of E?cacy of Transversus Abdominis Plane Block and Systemic Analgesia for Post-Operative Pain in Total Abdominal Hysterectomy: A Comparative Study - Menaka Viswanath; Ravikrishna Kalathur; K. Shanthini (Academia Anesthesiologica International, 2020)
Introduction: Management of post-operative Pain is gaining considerable attention with pain being recognized as the fifth vital sign. Post- operative pain management remains unresolved as pain is individualized and varies with surgery. The aim is to evaluate the analgesic efficacy of transverses abdominis plane block by continuous catheter technique and systemic analgesia for post-operative pain in total abdominal hysterectomy. Subjects and Methods: This randomized controlled trial was done in patients undergoing total abdominal hysterectomy via Pfannenstiel incision. Patients were assigned into 2 groups, systemic analgesics group (n=25) and TAP block group (n=25) randomly. Results: Out of 50 patients, 25 patients had systemic analgesics and 25 patients had TAP block. Demographics and surgical procedure times were comparable. Mean VAS pain score with coughing on day 1 and 2 in systemic analgesics group was 3.96 and 2.07 and in TAP block group were0.7 and 0.3. Meantime taken to mobilize the patient after the surgery in the systemic analgesics group was 30.7 hours and in TAP block group was 22.4 hour. 18 patients needed rescue medication in the systemic analgesics group, and 9 patients required rescue medication in the TAP block group. In group 16 patients with systemic analgesics had post-operative nausea and vomiting, and 5 patients in group block TAP. Conclusion: Continuous TAP block provides better pain relief, denoted by lower visual analogue scores and better recovery profile enhancing recovery in patients undergoing abdominal hysterectomy.